Une pale de roue à eau à deux jantes d’époque romaine découverte à Sorigny (Indre-et-Loire) - Florian Sarreste (Revue Archéologique du Centre de la France)
The archaeological rescue excavation carried out at “la Pièce des Viviers” (Sorigny, Indre-et-Loire) has revealed a succession of rural settlements from the second Iron Age and Roman Antiquity. The dig of the only well detected in the excavated area permitted the study waterlogged levels containing several organic remains dating to the beginning of Gallo-Roman period. Among the wood fragments studied by archaeodendrometry, a board, number Iso 53, has been found to be a waterwheel paddle. Its use can be situated between 60 AD and the end of the 2nd century AD. Very few examples of this kind of woodrest are known and the Sorigny one provides some new data on a facility so far unknown for the Roman period: waterwheels with assembled paddles.